2017
DOI: 10.18632/oncotarget.15577
|View full text |Cite|
|
Sign up to set email alerts
|

Solitary ground-glass opacity nodules of stage IA pulmonary adenocarcinoma: combination of 18F-FDG PET/CT and high-resolution computed tomography features to predict invasive adenocarcinoma

Abstract: To investigate the performance of combined 18F-FDG Positron Emission Tomography/Computed Tomography with high-resolution CT for differentiating invasive adenocarcinoma from adenocarcinoma in situ (pre-invasive lesion) or minimally invasive adenocarcinoma in stage IA lung cancer patients with solitary ground-glass opacity nodules. This retrospective study enrolled 58 consecutive stage IA pulmonary adenocarcinoma patients with solitary ground-glass opacity nodules. The characteristics and measurements of the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…Our results are consistent with previous studies. Shi et al revealed that there existed huge differences in the CT measurements of solitary GGNs between AIS-MIA and IAC [7]. Different from our study, they combined the AIS and MIA into one group.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Our results are consistent with previous studies. Shi et al revealed that there existed huge differences in the CT measurements of solitary GGNs between AIS-MIA and IAC [7]. Different from our study, they combined the AIS and MIA into one group.…”
Section: Discussioncontrasting
confidence: 79%
“…: (1) nodule patterns: pure ground-glass nodule (PGGN) or mixed ground-glass nodule (MGGN);(2) nodule shapes (round/oval shape or irregular shape); (3) pleural invasion (or not); (4) vascular invasion (or not); (5) lymphatic invasion (or not); (6) necrosis (or not);(7) diameter of the nodule (largest diameter on the axial section) ; (8) diameter of the solid component (largest diameter of solid component on the axial section; (9) proportion of the solid component (< 50% or > 50%); (10) the border of the nodule was defined or undefined; (11) the margin of the nodule (smooth, lobulate, or spiculate); (12) vascular convergence sign (or not); (13) air-bronchograms (direct involvement of bronchiole, in the GGO component or in the solid component, no); (14) vacuole sign (or not, pointlike/translucent/low-density shadows); (15) pleural indentation (or not). Besides, CT radiodensity values were recorded (for PGGN, the value of GGO component; for MGGN, the value of solid component).…”
mentioning
confidence: 99%
“…Additionally, the napkin-ring sign, plaque CT value and degree of coronary artery stenosis were also analyzed by multivariate logistic regression analysis. The statistical method was reported previously (21). Briefly, a logistic regression equation was formed by multivariate regression analysis, and the exact pair-matched data of the napkin-ring sign and plaque CT value of the 68 plaques were backtested via the equation to compute exact probabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutions in the radiological features analysis of the nodule would probably help us determining lesion invasiveness and surgical requires (13,14).…”
Section: Introductionmentioning
confidence: 99%